2007
DOI: 10.1016/j.jml.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The return of the repressed: Abandoned parses facilitate syntactic reanalysis☆

Abstract: Two eye movement experiments examined effects on syntactic reanalysis when the correct analysis was briefly entertained at an earlier point in the sentence. In Experiment 1, participants read sentences containing a noun phrase coordination/clausal coordination ambiguity, while in Experiment 2 they read sentences containing a subordinate clause object/main clause subject ambiguity. The critical conditions were designed to induce readers to construct the ultimately correct analysis just prior to being garden-pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 75 publications
0
18
1
Order By: Relevance
“…Several recent studies have corroborated Christianson et al's observation that misanalyses appear to linger (Kaschak & Glenberg, 2004;Staub, 2007a;Sturt, 2007;van Gompel, Pickering, Pearson, & Jacob, 2006), though researchers differ on why this might be. For instance see also Christianson et al, 2006) attributed the lingering effect to a failure to fully reanalyze the partial, and ultimately incorrect, syntactic structure constructed during the initial parse of the garden path sentence.…”
Section: ) Exemplifies This Assumptionmentioning
confidence: 73%
“…Several recent studies have corroborated Christianson et al's observation that misanalyses appear to linger (Kaschak & Glenberg, 2004;Staub, 2007a;Sturt, 2007;van Gompel, Pickering, Pearson, & Jacob, 2006), though researchers differ on why this might be. For instance see also Christianson et al, 2006) attributed the lingering effect to a failure to fully reanalyze the partial, and ultimately incorrect, syntactic structure constructed during the initial parse of the garden path sentence.…”
Section: ) Exemplifies This Assumptionmentioning
confidence: 73%
“…2001; Kaschak and Glenberg 2004; Lau and Ferreira 2005; van Gompel et al. 2006; Staub 2007; Sturt 2007) have suggested that an abandoned parse of a sentence may be maintained, with some level of activation, along with the correct parse. For example, van Gompel et al.…”
Section: Is There Other Evidence For Parallelism?mentioning
confidence: 99%
“…Hopf et al 2003). Sticking to behavioral data, several studies (Christianson et al 2001;Kaschak and Glenberg 2004;Lau and Ferreira 2005;van Gompel et al 2006;Staub 2007;Sturt 2007) have suggested that an abandoned parse of a sentence may be maintained, with some level of activation, along with the correct parse. For example, van Gompel et al (2006) had participants complete sentence fragments containing an optionally transitive verb, for example, When the doctor was visiting.…”
Section: Does Parallelism Really Predict Competition?mentioning
confidence: 99%
“…This effect was found on both first pass time and go-past time, and the presence of either did not eliminate the garden path effect. In fact, the garden path effect was numerically smaller when either was absent compared to when either was present (366 ms vs. 368 ms), which was interpreted in terms of the initial syntactic analysis and the reanalysis [25]. Regardless of whether the word either was present or absent, readers adopted the NP-coordination analysis in the ambiguous region, and yet this analysis was abandoned when the S-coordination was confirmed.…”
Section: Introductionmentioning
confidence: 94%